The tasks presentation relating the academic degree of the football coaches - I. Mesquita; C. Farias; A. Rosado; F. Pereira; M.P. Moreno (Asociación Española de Ciencias del Deporte, 2010)
The purpose of the present study was to characterize the pedagogical interventions of the football coaches during the task presentations, based on the coaches' specialized academic degree. The sample consisted of twelve football coaches (n=12). The dependent variables were as follows: the tasks' type nature (analyzed by Rink's system categories, 1993); the task explicitness level (analyzed by Silverman, Kullina y Crull's system categories, 1995). The independent variables of the study were the specialized academic degrees, differentiating between those with a graduation in physical education and those without. The results show that coaches predominantly present information tasks and the refinement, extension and application tasks were rarely used, which suggests a bad didactic development of the content. As to the task explicitness level, the majority of coaches' instructions are given through general instruction, which privileged clarifying the task outcome and situation tasks and some information about criteria-form and the outcome. The   coaches with a graduation in physical education use more refinement tasks and task explicitness, and refer significantly more to criteria-form than coaches with no graduation. Key Words:coach; academia degree; instructional tasks; task explicitness; football.